E-guided discovery module for cartesian coordinates topic in junior high school - Permatasari, Dian; Herman, Tatang (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
Guided Discovery learning is an approach that actively engages students by allowing them to discover and investigate concepts independently. However, the development of guided discovery integrated with technology, especially on Cartesian coordinates, is still limited and has not been widely explored. likeTherefore, this study explores the ıntegrating guided discovery approach in e-module for cartesian coordinates topıc of junior high school, involving one teacher and 32 students as research subjects. Qualitative data analysis was conducted through documentation and interviews, which were then organized into data reduction, display, and verification steps. The results indicate that the E-Guided Discovery Module effectively enhances students' interest and understanding of mathematical concepts, although several areas require technical and pedagogical improvements. Recommendations for further development include enhancing the user interface, adding interactive features, and developing additional guidance. The E-Guided Discovery Module is an effective tool for improving students' mathematics learning, with the teacher's role being crucial in providing necessary guidance and support.